The impact of malocclusion on the prevalence of pain-related temporomandibular disorders in children and adolescents: a systematic review - Szyszka-Sommerfeld, Liliana; Sycińska-Dziarnowska, Magdalena; Gerreth, Karolina; Spagnuolo, Gianrico; Woźniak, Krzysztof; Czajka-Jakubowska, Agata (Frontiers in Neurology, 2025)
BackgroundThe connection between occlusion and temporomandibular disorders (TMD) remains a topic of discussion, and current research does not provide a definitive answer. Pain-related TMD are the most common types of TMD. They include myalgia, arthralgia, and headaches attributed to TMD. This systematic review aims to synthesize the current scientific evidence regarding impact of malocclusion on the prevalence of pain-related TMD in individuals under 18 years.MethodsThe study was based on a searching of the PubMed, Scopus, Embase, and Web of Science databases. Selection was limited to studies that explored the link between malocclusion and pain-related TMD in young individuals. The Newcastle-Ottawa Scale (NOS) was used to evaluate the quality of the selected research. The certainty of evidence was assessed using the Grading Recommendations Assessment, Development and Evaluation (GRADE) approach. A visual representation of the screening and inclusion processes was created using a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram. The information from the research was then summarized in a descriptive format.ResultsOut of 868 potentially relevant articles initially identified, 13 studies were selected based on the inclusion criteria. The majority of these studies were determined to be of moderate quality, according to the NOS assessment. The certainty of evidence was assessed as low, according to the GRADE approach. Most of the studies showed that malocclusion may be associated with TMD-pain signs/symptoms in children and adolescents. The most frequent relationship was found between the prevalence of pain-related TMD and posterior crossbite, Class II malocclusion, Class III malocclusion, and anterior open bite.ConclusionCertain types of malocclusion may have an impact on the prevalence of some TMD-pain signs and symptoms in young individuals. However, given the limited reliability of existing research and the inconsistencies observed across studies, additional well-structured, long-term investigations are necessary.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024570950.